If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 3y = 162 Solving 12x + 3y = 162 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 12x + 3y + -3y = 162 + -3y Combine like terms: 3y + -3y = 0 12x + 0 = 162 + -3y 12x = 162 + -3y Divide each side by '12'. x = 13.5 + -0.25y Simplifying x = 13.5 + -0.25y
| X/8+2=14 | | m+10-14m=-5 | | (3-3/2y)^2 | | -3x+3(5+13)=3 | | x-3+5x= | | 4k-28k=-49 | | 7x-4/5x=6 | | H/5+3=-6 | | 11(4-6x)+5(13y+1)=9 | | 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 |